Hadis Khilâfah dan Relasinya terhadap Kontestasi Politik Hizbut Tahrir Indonesia (HTI) Pasca-Perpu Nomor 2 Tahun 2017 - Muqtada, Muhammad Rikza (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2018)
After the dissolution of Hizbut Tahrir Indonesia (HTI) by the Ministry of Law and Human Rights, sympathizers of HTI tried to appeal in various ways. One of them is to build the opinions through the dakwah media of HTI about the authenticity of al-Khilâfah al-Islâmîyah sources in the religious narratives. This propaganda means that the political system fought for by HTI is a part of the Islamic Shari‘a which have to be defended, rejecting it means kufr. However, the legality of khilâfah’s source is problematic. The Qur’an does not mention it, while the hadith that mentions the khilâfah is more problematic. The hadith of khilâfah only narrated by Ahmad b. Hanbal on his book. This Ḥadîth arises due to the attitude of Ḥabîb b. Salîm who looked for face in front of ‘Umar b. Abd al-‘Azîz as the khalifah claimed by ‘alâ minhâj al-nubuwwah. The triumph at that time was dreamed by HTI to be re-realized. To realize that vision, HTI interprets the religious texts to the political platform that means has mixed religious functions and political functions become one.",